The Development of A Knee Orthotic to Prevent Falling Due to Buckling Among Elderlies: Mechatronic and Robotics - Veeran, Yogeswaran; Tee, Kian Sek (Evolution in Electrical and Electronic Engineering, 2021)
Many elderlies are living alone in their home. If an elderly falls due to buckling, it may cause severe bone injuries and maybe be difficult to request help. A mechatronic orthotic is designed and developed to lock the knee movement during the detection of buckling. A ratchet mechanism is deployed to lock the knee orthotic from moving during fall occurs. Data is obtained from all the axis of an Inertia Movement Unit (IMU). To differentiate the normal walking pattern angle and falling pattern angle from the IMU sensor X, Y and Z axis reading are monitored between the range of the Upper Falling Threshold (UFT) value and Lower Falling Threshold (LFT) value which are used to identify falling during walking phase.